Requirements and concepts for future automotive electronic architectures from the view of integrated safety - Chen, Xi (KIT Scientific Publishing, 2008)
In this dissertation, concepts of the electronic architecture of automotive Integrated Safety System are developed as a cooperative approach of engineering process, dependable hardware architecture and software platform. The development process covers distributed rapid prototyping with virtual front-loading and correct-by-construction. Concepts of fault tolerant hardware architecture and dependability software services are discussed with design guidelines.